2021
DOI: 10.18632/aging.202743
|View full text |Cite
|
Sign up to set email alerts
|

Centenarians in nursing homes during the COVID-19 pandemic

Abstract: Background: Centenarians are known to be successful agers compared to other older adults.Objective: The objective of the present study was to compare coronavirus disease (COVID-19) symptoms and outcomes in centenarians and other residents living in nursing homes. Design-Setting-Subjects-Methods: A retrospective multicenter cohort study was conducted using data from 15 nursing homes in the Marseille area. Older residents with confirmed COVID-19 between March and June 2020 were enrolled. The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…There were 15 residents of extreme ages that participated in our study. The majority were female (12 women and 3 men) which is consistent with the literature for nonagenarians and centenarians ( Table 1 ) [26] . In total there were 8 centenarian included, representing 9 of the 12 centenarians in the LTC facility at the time of the outbreak and all of the centenarians approached for consent.…”
Section: Resultssupporting
confidence: 90%
“…There were 15 residents of extreme ages that participated in our study. The majority were female (12 women and 3 men) which is consistent with the literature for nonagenarians and centenarians ( Table 1 ) [26] . In total there were 8 centenarian included, representing 9 of the 12 centenarians in the LTC facility at the time of the outbreak and all of the centenarians approached for consent.…”
Section: Resultssupporting
confidence: 90%
“…Although widely emphasized by the media [ 5 ], the resilience of centenarians to COVID-19 remains a controversial issue that is now increasingly attracting researchers. Couderc et al [ 6 ], in a study on 321 nursing home residents in Southern France, including 12 centenarians, reported a higher mortality rate among these centenarians (50% vs 24.6%) compared with other younger residents, corresponding to one of the lowest survival rates compared with other published series [ 7 ]. Similarly, Marcon et al [ 8 ], in a study on 42 centenarians from North-Eastern Italy as part of the CaT (Centenari a Trieste) project, observed that COVID-19-related mortality among long-lived individuals was higher than that of the population between 50 and 80 years of age, and that the mortality rate among the oldest women exceeded that of men.…”
Section: Introductionmentioning
confidence: 99%
“…8 Throughout the first year of the pandemic, both the pandemic itself and visiting bans have been linked to increased risk of depressive symptoms in residents 192 in addition to worsening of preexisting depression. 193 Similarly, the prevalence of depressive symptoms significantly increased in comparison to prepandemic levels in one longitudinal study, 194 and studies have suggested a decline in cognitive function and an increase in depressive symptoms following the strict lockdown measures. 195 Qualitative work has demonstrated the influence of strict lockdowns and visiting bans on feelings of loneliness in nursing home residents.…”
Section: Psychological Impact On Residentsmentioning
confidence: 94%